2023
DOI: 10.1111/exd.14791
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐36 cytokines are overexpressed in the skin and sera of patients with bullous pemphigoid

Abstract: Bullous pemphigoid (BP) is an autoimmune bullous disease, characterized by autoantibodies targeting BP180 and BP230. The role of interleukin (IL)-36, a potent chemoattractant for granulocytes, in BP remains elusive.The expression of IL-36 cytokines (IL-36α, β, γ) and their antagonists (IL-36Ra and IL-38) was analysed in the skin and serum samples of patients with BP (n = 31), psoriasis (n = 10) and healthy controls (HC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In addition, the role of IL-38 in psoriasis has been extensively explored, with IL-38 expression levels is correlated with the severity of psoriasis. 11,[60][61][62][63][64] Cytokines secreted by Th1 and Th17 cells contribute to the pathogenesis of psoriasis, and IL-38 is involved in regulating the secretion of IL-17 and IL-22 by Th17 cells. 65,66 Moreover, Th17 cells are involved in the progression of various autoimmune diseases, 60,67,68 such as rheumatoid arthritis, 26,36 primary Sjögren's syndrome, 69,70 inflammatory bowel disease, 8 ankylosing spondylitis, 71 allergic rhinitis, 72 glaucoma, 73 septic dermatitis, multiple sclerosis, and autoimmune thyroid disease, [74][75][76][77][78][79][80] suggesting that IL-38 may play a key role in autoimmune diseases.…”
Section: The Role Il-38 In Autoimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the role of IL-38 in psoriasis has been extensively explored, with IL-38 expression levels is correlated with the severity of psoriasis. 11,[60][61][62][63][64] Cytokines secreted by Th1 and Th17 cells contribute to the pathogenesis of psoriasis, and IL-38 is involved in regulating the secretion of IL-17 and IL-22 by Th17 cells. 65,66 Moreover, Th17 cells are involved in the progression of various autoimmune diseases, 60,67,68 such as rheumatoid arthritis, 26,36 primary Sjögren's syndrome, 69,70 inflammatory bowel disease, 8 ankylosing spondylitis, 71 allergic rhinitis, 72 glaucoma, 73 septic dermatitis, multiple sclerosis, and autoimmune thyroid disease, [74][75][76][77][78][79][80] suggesting that IL-38 may play a key role in autoimmune diseases.…”
Section: The Role Il-38 In Autoimmune Diseasesmentioning
confidence: 99%
“…In patients with systemic lupus erythematosus (SLE), serum levels of IL‐38 are significantly elevated and its high levels are associated with the remission of SLE‐related symptoms, including proteinuria, leukocyturia and skin lesions, and it has also been reported that IL‐38 is involved in the progression of SLE by regulating the NF‐κB signaling pathway, 57–59 suggesting that IL‐38 may play a play a protective role in SLE. In addition, the role of IL‐38 in psoriasis has been extensively explored, with IL‐38 expression levels is correlated with the severity of psoriasis 11,60–64 . Cytokines secreted by Th1 and Th17 cells contribute to the pathogenesis of psoriasis, and IL‐38 is involved in regulating the secretion of IL‐17 and IL‐22 by Th17 cells 65,66 .…”
Section: Role Of Ll‐38 In Related Diseasesmentioning
confidence: 99%
“…A recent study found that NS patients have a predominant IL-36 immune signature ( 30 ), with a clinical trial set to test Spesolimab in NS patients (NCT05856526). Moreover, IL-36 cytokines were overexpressed in BP and PN patient skin ( 31 , 59 ). Similarly, IL-36 expression was associated with inflammation in other eosinophilic disorders (e.g., AR and eosinophilic pustular folliculitis) and induced the in vitro survival, adhesion, migration, and activation of eosinophils, suggesting that IL-36R signaling is an important mediator of eosinophilic responses ( 42 , 60 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous basic research initially investigated the coexisting mechanism of BP and psoriasis. Multiple investigations have shown similar dysregulated cytokine expression and inflammatory responses in the immune systems of psoriasis and bullous pemphigoid patients ( 27 , 31 , 32 ). For instance, IL-1 was found necessary for the development of psoriatic lesions such as epidermal proliferation and differentiation ( 31 ), and the level of IL-1b was found to be higher in blister fluid than in BP serum ( 33 ).…”
Section: Discussionmentioning
confidence: 99%